Implications of Islamic Theology on The Psychoanalysis of The Character Ember from The Film Elemental: Forces of Nature - Haryanto, Sri; El Syam, Robingun Suyud; Munawaroh, Hidayatu (Universitas Muhammadiyah Yogyakarta, 2024)
Apart from being an entertainment source, movies can have a deep meaning that benefits life. Some films offer a multidimensional perspective that can be viewed from various aspects. This research explores the psychological condition of Ember, the main character in the film